2016
DOI: 10.1080/03004279.2016.1171572
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and self-esteem: ‘Jonny’s story’

Abstract: Previous research has proposed that physical exercise can raise self-esteem. This paper will examine the extent to which physical activity interventions, within one case study primary school supported the development of self-estee of a ju io ea hild o e a pe iod of fi e o ths. Jo as years old when the physical activity intervention commenced. His name is a pseudonym to protect his o fide tialit . Jo had ee easu ed o the s hool s ell ei g easu e e t s ale a d as reported to have a very low self-esteem, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…There are many studies in the literature that show a relationship between physical activity and self-esteem and between physical activity and academic achievement. Despite the positive relationship between physical activity and academic achievement and self-esteem in past studies [28,30,31], very little studies have been found on the type, severity and duration of physical activity that may be appropriate [32,33]. In this respect, it is evaluated that it is important that our work is focused on kids' athletics, that a specific program is introduced, and that there are no studies that investigate the effects of kids' athletic practices alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the literature that show a relationship between physical activity and self-esteem and between physical activity and academic achievement. Despite the positive relationship between physical activity and academic achievement and self-esteem in past studies [28,30,31], very little studies have been found on the type, severity and duration of physical activity that may be appropriate [32,33]. In this respect, it is evaluated that it is important that our work is focused on kids' athletics, that a specific program is introduced, and that there are no studies that investigate the effects of kids' athletic practices alone.…”
Section: Discussionmentioning
confidence: 99%
“…Training was done on discus throw and shot put. At the end of the term; John is raised literacy and mathematic grades and led to a small but significant increase in self-esteem [28].…”
Section: Discussionmentioning
confidence: 99%